Rainbow Connection Number of Double Quadrilateral Snake Graph - Yuniarti, Ervie Yuniarti Astika Mustafaputri; Nurwahyu , Budi; Massalesse, Jusmawati (Jurnal Matematika, Statistika dan Komputasi, 2023)
Let graph G = be a non trivial connected graph. A graph G with edge coloring is called a rainbow connection, if for every pair of vertices on a path has a different color. The rainbow connection number denoted by is the minimum color needed to make graph G rainbow connection. In this study, we will determine the rainbow connection number of double quadrilateral snake graph and alternate double quadrilateral snake graph. The research results show that while if and if